Self‐Sorting Effects in the Self‐Assembly of Metallosupramolecular Rhombi from Chiral BINOL‐Derived Bis(pyridine) Ligands. Issue 1 (4th November 2013) - Gütz, Christoph; Hovorka, Rainer; Stobe, Caroline; Struch, Niklas; Topić, Filip; Schnakenburg, Gregor; Rissanen, Kari; Lützen, Arne
Abstract: Four BINOL‐based bis(4‐pyridyl) ligands were synthesised in enantiopure and racemic form. These ligands form metallosupramolecular [(dppp)2 M2 L2 ] rhombi with cis ‐protected [(dppp)Pd] 2+ and [(dppp)Pt] 2+ ions. In principle, racemic ligands can self‐assemble into three stereoisomeric rhombi. The degree of self‐sorting in the self‐assembly process crucially depends on the substitution pattern and the resulting bend angle of the V‐shaped ligands as well as the degree of steric crowding within the assembly when racemic ligands are used. Thus, these processes either lead to homochiral assemblies in a narcissistic self‐recognition manner, to heterochiral assemblies in a social self‐discriminating manner, or proceed in a nonselective fashion as evidenced by NMR spectroscopy, mass spectrometry and single‐crystal X‐ray diffraction. Abstract : Self‐assembly of racemic bis(4‐pyridyl) ligands based on a 1, 1′‐binaphthyl scaffold leads to dinuclear metallosupramolecular rhombi. Whereas 6, 6′‐substituted derivatives do not show any self‐sorting, giving rise to a statistical mixture of stereoisomers, their 3, 3′‐difunctionalised isomers self‐sort in a preferred social self‐discrimination or in a highly selective self‐recognition manner.